2001
DOI: 10.1002/1521-3773(20010618)40:12<2339::aid-anie2339>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Pentacoordination of Silicon by Four Covalent Si−S Bonds and One Covalent Si−C Bond

Abstract: The zwitterionic compounds 1 and 2 are the first pentacoordinate silicates with covalent SiS4C skeletons. They were characterized by crystal‐structure analyses and NMR spectroscopic studies. Although pentacoordination of silicon is usually favored by ligand atoms of high electronegativity, the structural data of both 1 and 2 are consistent with the presence of five covalent bonds to the silicon atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The ability of silicon to expand its valence is central to the nucleophilic activation and substitution of organosilicon compounds . Many stable well-characterized pentavalent species have been reported; most carry multiple electronegative heteroatoms such as fluorine, oxygen, and/or nitrogen. Also, hexacoordinate silicates are known such as SiF 6 2- and those with a SiO 6 , SiN 2 O 4 , or SiN 2 O 3 C core. ,5e,g Tacke et al showed that incorporating the counterion gives stable zwitterionic silicates, including the first species with SiS 2 O 2 C and SiS 4 C skeletons, 5c,f while others are even soluble in water 5h. Fewer silicates are known with multiple carbon substituents due to their anticipated lower stability.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of silicon to expand its valence is central to the nucleophilic activation and substitution of organosilicon compounds . Many stable well-characterized pentavalent species have been reported; most carry multiple electronegative heteroatoms such as fluorine, oxygen, and/or nitrogen. Also, hexacoordinate silicates are known such as SiF 6 2- and those with a SiO 6 , SiN 2 O 4 , or SiN 2 O 3 C core. ,5e,g Tacke et al showed that incorporating the counterion gives stable zwitterionic silicates, including the first species with SiS 2 O 2 C and SiS 4 C skeletons, 5c,f while others are even soluble in water 5h. Fewer silicates are known with multiple carbon substituents due to their anticipated lower stability.…”
Section: Introductionmentioning
confidence: 99%
“…The axial N‐Si‐N angles amount to 163.93(7) ( 4 ) and 163.59(9)° ( 5 ), and the sum of the equatorial bond angles is 360° for both compounds (Berry distortion: 21.0/21.9 %) . The Si−El distances of the five‐coordinate silicon(IV) compounds 4 (El=S, 2.1606(7) Å) and 5 (El=Se, 2.3082(9) Å) are slightly longer (shorter) than those of four‐coordinate (six‐coordinate) silicon(IV) compounds and compare well with the equatorial Si−El bond lengths of other neutral and zwitterionic five‐coordinate silicon(IV) compounds, such as 6 , 7 , 8 , and 9 – 12 . Also, the equatorial Si−S bond length of 4 is very similar to those of compounds 13 and 14 , which are, to the best of our knowledge, the only cationic five‐coordinate silicon(IV) compounds with silicon–sulfur single bonds reported in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…The 29 Si NMR resonance of −150.8 ppm for 3 (in CD 3 CN) is comparable to that of −148.3 ppm (in [D 6 ]DMSO) reported for [Si(Tm Ph ) 2 ] 2+ dications (Tm Ph =hydro‐tris(phenylthioimidazolyl)borate), supporting the presence of a six‐coordinate silicon atom in 3 . In contrast, 29 Si NMR resonances of the four‐coordinate (Figure a) and five‐coordinate (Figure b) silicon bis(dithiolene)s were reported at +45.4 ppm and −57.2 ppm, respectively. Five‐coordinate 29 Si resonances were not observed in variable‐temperature (VT) 29 Si NMR experiments (Figures S4–S7 in the Supporting Information), which does not support an equilibrium between 3 and the five‐coordinate silicon species (which could possibly be produced through partial dissociation of a dithiolene ligand in solution).…”
Section: Figurementioning
confidence: 99%
“…While being similar to those in [Si(Tm Ph ) 2 ] 2+ dications (2.3176 Å, av), the Si−S bonds of 3 [2.3195(12)–2.3374(12) Å] are somewhat shorter than that in [3‐H] 2− (2.3894 Å), and considerably longer than that [2.1381(6) Å] in four‐coordinate silicon bis(dithiolene), Si[S 2 ( ο ‐C 6 H 4 )] 2 (Figure a) . The zwitterionic pentacoordinate silicon bis(dithiolene) (Figure b) contains both [2.1590(9) Å, av] equatorial and [2.3076(7) Å, av] axial Si−S bonds …”
Section: Figurementioning
confidence: 99%